A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Temperature-dependent development and reproduction of Tarsonemus confusus (Acari: Tarsonemidae): an important pest mite of horticulture - Litao Li; Lichen Yu; Limin He; Xiong Zhao He; Rui Jiao; Changxin Xu (Experimental and Applied Acarology, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Dynamic mechanical behavior of coral rock subjected to high strain rate loading - Houzhen Wei; Linjian Ma; Jiawen Wu; Jin Yu; Zeng Li; Rui Xu (Marine Geophysical Research, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Autism spectrum disorder-like behavior induced in rat offspring by perinatal exposure to di-(2-ethylhexyl) phthalate - Yao Li; Yun Zhao; Yu Lu; Xianxian Lu; Yingdan Hu; Qiulin Li; Menglei Shuai; Rui Li (Environmental Science and Pollution Research, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Alleviative Effects of Exercise on Bone Remodeling in Fluorosis Mice - Rui Li; Zeen Gong; Yanghuan Yu; Ruiyan Niu; Shengtai Bian; Zilong Sun (Biological Trace Element Research, 2022)

Projected change in precipitation forms in the Chinese Tianshan Mountains based on the Back Propagation Neural Network Model - Rui Ren; Xue-mei Li; Zhen Li; Lan-hai Li; Yi-yu Huang (Journal of Mountain Science, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Existing form and distribution of fluorine and phosphorus in phosphate rock acid-insoluble residue - Rui Li; Weilong He; Jiangfei Duan; Shengxia Feng; Ziyu Zhu; Yu Zhang (Environmental Science and Pollution Research, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)